Battery Energy Storage System Placement And Sizing In Distribution Networks - Sorokin Dmitry (E3S Web of Conferences)
The article discusses the methodology for selecting installation locations and parameters of battery energy storage systems (BESS) in electrical distribution networks. The methodology is applicable to BESS which implement the functions of ensuring the reliability of power supply to consumers (use of BESS as a backup or emergency source of power supply), as well as the function of regulating voltage levels in the electrical network (regulating reactive power by the BESS inverter).